B-cell survival factors in autoimmune rheumatic disorders. (August 2015) - Morais, Sandra A.; Vilas-Boas, Andreia; Isenberg, David A.
Autoimmune rheumatic disorders have complex etiopathogenetic mechanisms in which B cells play a central role. The importance of factors stimulating B cells, notably the B-cell activating factor (BAFF) and A proliferation inducing ligand (APRIL) axis is now recognized. BAFF and APRIL are cytokines essential for B-cell proliferation and survival from the immature stages to the development of plasma cells. Their levels are increased in some subsets of patients with autoimmune disorders. Several recent biologic drugs have been developed to block this axis, namely belimumab [already licensed for systemic lupus erythematosus (SLE) treatment], tabalumab, atacicept and blisibimod. Many clinical trials to evaluate the safety and efficacy of these drugs in several autoimmune disorders are ongoing, or have been completed recently. This review updates the information on the use of biologic agents blocking BAFF/APRIL for patients with SLE, rheumatoid arthritis, Sjögren's syndrome and myositis.